Methodological Approaches to Pedagogical Control of Motor Readiness of Girls Aged 6-10 - O. Ivashchenko (OVS LLC, 2017)
The objective is to determine methodological approaches to pedagogical control of motor readiness of girls aged 6-10.  Materials and methods. The participants in the experiment were girls aged 6 (n = 36), aged 7 (n = 48), aged 8 (n = 57), aged 9 (n = 38), aged 10 (n = 46). To achieve the tasks set, the research relied on the following methods: analysis of scientific and methodological literature, pedagogical testing and methods of mathematical statistics. The testing program consisted of well-known tests. As a modeling method, the research used factor and discriminant analyses. Results. The analysis of the factor and discriminant model of motor readiness has provided information necessary for making decisions in physical education management, as well as for developing effective physical training programs for girls aged 6-10. Conclusions. The girls aged 6-10 show a multifactorial structure of motor readiness. By analyzing the common features, the research has defined informative tests of motor readiness control for each age group. During the analysis, the research has calculated the canonical discriminant function coefficients (non-standardized), which act as the factors of specified variable values included in the discriminant functions. On their basis, it is possible to classify the girls by their level of motor readiness according to the age, which is of practical value.